Library Management Strategy With Library Café Concept At SMK Nasional Malang - Kartika, Anggi; Effendi, Anggi Laila; Nurani, Budi; Prestiadi, Dedi; Syaiful, Syaiful (Proceedings Series of Educational Studies, 2024)
The library as a means of information and learning resources at SMK Nasional Malang has a design with the concept of a librabry café that allows students to be able to read books casually while eating, drinking and listening to music so as to create a comfortable impression. But besides that, it causes noise and can interfere with the reader's concentration. Therefore, good library management is needed to condition the harmony between café activities and reading needs in the library. This article aims to; 1) providing an explanation of library management with the concept of a library café at SMK Nasional Malang; 2) provide explanations related to supporting factors, inhibitions and challenges in library management with the concept of library café at SMK Nasional Malang. This article applies a descriptive qualitative method using observation and interviews as a research approach. With two data sources, namely the person in charge of the Malang National Vocational School Library as a source of primary data for research and relevant references as secondary data sources. The results of the study show that the management of the library with the concept of a library café at SMK Nasional Malang implemented by the school has been well organized and implemented. Meanwhile, it was found that infrastructure and library management resources are one of the driving and inhibiting factors in library management with the concept of library café. Keywords: management, library, library café